Pembelajaran Kosa Kata Bahasa Arab Secara Aturan Kluster Semantik dan Aturan Kluster Bebas (Sains Humanika, 2014)
Many Arabic language books use semantic clustering in presenting their vocabularies. However, some language experts suggest the use of semantically unrelated clustering due to a higher contribution in memorizing vocabularies among students. This study aims to investigate on which clustering has a higher contribution in memorizing vocabularies among students. The specific objectives of this study are; (a) to identify the level of students’ achievement in memorizing vocabularies using both techniques in a long-term test and a short-term test; and (b) to identify students’ achievement differences using both techniques in both tests. This study is a quasi-experimental study which using a short term and a long term post-test. This group of students was exposed to vocabularies using semantic clustering and semantically unrelated clustering. The short term post test was administered after the students were exposed with both techniques, while the long term post-test was used after seven days of the exposure. This study found that students’ achievement using semantic clustering was moderate for both tests. Meanwhile, students’ achievement using semantically unrelated clustering was very good in the short term test and good in the long term test. On the other hand, the t-test analysis showed that there are significant differences between both techniques, which students’ achievement using semantically unrelated clustering is statistically and significantly higher than students’ achievement using semantic clustering for both short and long term post-tests. Therefore, this study suggests that the semantically unrelated clustering technique needs to be used in learning Arabic vocabularies among students.
Keywords: Arabic vocabularies learning; vocabularies learning strategy; vocabularies acquisition; semantic clustering; semantically unrelated clustering